2022
DOI: 10.20517/energymater.2021.07
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing cycle life of nickel-rich LiNi0.9Co0.05Mn0.05O2 via a highly fluorinated electrolyte additive - pentafluoropyridine

Abstract: Y, Zheng J. Enhancing cycle life of nickel-rich LiNi 0.9 Co 0.05 Mn 0.05 O 2 via a highly fluorinated electrolyte additive -pentafluoropyridine. Energy

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 27 publications
(35 reference statements)
0
18
0
Order By: Relevance
“…Through fitting of the experimental EIS data using the equivalent circuit model in Figure 6D, the charge transfer resistance (R ct ) of 93.3 Ω is obtained for the LMO anode before cycling, while the R ct of the LMO@CNF is much lower at 48.5 Ω, [Figure 6A], indicating its higher electron transfer rate at the electrode interface. The Li-ion diffusion rate can be calculated by [30,31] :…”
Section: Resultsmentioning
confidence: 99%
“…Through fitting of the experimental EIS data using the equivalent circuit model in Figure 6D, the charge transfer resistance (R ct ) of 93.3 Ω is obtained for the LMO anode before cycling, while the R ct of the LMO@CNF is much lower at 48.5 Ω, [Figure 6A], indicating its higher electron transfer rate at the electrode interface. The Li-ion diffusion rate can be calculated by [30,31] :…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the disorder can disrupt the transport path of lithium ions and with the effect of the electrostatic repulsion between transition metal elements, the Li mobility can be significantly reduced. Simultaneously, the Li slab space can also be reduced due to the disorder effect, resulting in a high activation barrier to Li-ion diffusion [91] . To address these challenges, the doping of polymetallic elements was developed to stabilize the crystal structure, and thus the disadvantage of single doping can be avoided with additional advantages, e.g., enhanced electrical properties.…”
Section: Typical Lib Electrode Materialsmentioning
confidence: 99%
“…In addition, the side reactions of the interface between the FSEs and the composite electrode are also a thorny issue during the battery cycling, which involves inferior anodic stability and chemical incompatibility of FSEs and the high voltage cathode materials. [ 64–67 ] The uneven current distribution and sluggish Li + transfer and interface side reaction are the dominant reasons to deteriorate the electrochemical performance of FLBs, especially when the batteries are in state‐of‐charge (SOC) or at high temperature. It is worth noting that FLBs inevitably undergo more complex external/internal stresses such as folding, bending, and stretching frequently, which are fatal to the electrochemical performance and safety of FLBs.…”
Section: Interface Challenges and Optimization Strategies In Flbsmentioning
confidence: 99%